2019
DOI: 10.3846/btp.2019.19
|View full text |Cite
|
Sign up to set email alerts
|

Islamic stock market and sukuk market development, economic growth, and trade openness (the case of Indonesia and Malaysia)

Abstract: This study was conducted in order to analyse the two-way relationship between the Islamic stock market and sukuk market development, and economic growth. this study also analyses whether trade openness influences the development of the Islamic stock market and sukuk market, and economic growth. VAR (Vector Auto Regressive), VECM (Vector Error Correction Model), and a Granger Causality Test used to test the hypothesis. Using Indonesia and Malaysia as the sample countries and from February 2008 to December 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 48 publications
(55 reference statements)
2
14
0
2
Order By: Relevance
“…Kim and McKenzie (2008) provided an explanation that in a relatively advanced capital market, foreign investors had a relatively important role and would tend to be more flexible in managing the cash flow. This finding is also supported by Park (2013), Muharam, Anwar and Robiyanto (2019) who found that stock market integration in Indonesia, Malaysia, Philippines, and Thailand tended to be different from other Asian countries. Findings by Najmudin et al (2019), Wahyudi et al (2018), also supported the previous findings, concluding that the Indonesian and Philippine stock markets tended to be segmented compared to other ASEAN stock markets.…”
Section: Asian Stock Markets Integrationsupporting
confidence: 65%
“…Kim and McKenzie (2008) provided an explanation that in a relatively advanced capital market, foreign investors had a relatively important role and would tend to be more flexible in managing the cash flow. This finding is also supported by Park (2013), Muharam, Anwar and Robiyanto (2019) who found that stock market integration in Indonesia, Malaysia, Philippines, and Thailand tended to be different from other Asian countries. Findings by Najmudin et al (2019), Wahyudi et al (2018), also supported the previous findings, concluding that the Indonesian and Philippine stock markets tended to be segmented compared to other ASEAN stock markets.…”
Section: Asian Stock Markets Integrationsupporting
confidence: 65%
“…The findings support Tandelilin's (2020) theory, which notes that macroeconomic factors empirically influence capital market conditions in many countries. These findings support the findings of Muharam, Anwar, and Robiyanto's (2019) which found a causal association between economic growth and the creation of the Malaysian sukuk sector. Said and Grassa (2013) further posit that GDP per capita has a positive impact on the sukuk market's growth, Abrorov (2020) found that sukuk has a positive impact on the economy as evidenced by sukuk emission as a factor in rising Muslim countries' income.…”
Section: Gross Domestic Productsupporting
confidence: 91%
“…The results highlighted that only sovereign Á sukūk positively affects economic growth, implying that it is comparatively more productive than conventional sovereign bonds. Lastly, in a recent study from 2008 to 2017, Muharam et al (2019) pointed out that economic growth is found to have no significant effect on the Á sukūk market in Malaysia, while, in Indonesia, economic growth exerts a significant IJIF 13,1 negative long-term effect on the Á sukūk market using vector error correction model (VECM). Moreover, Granger-causality results suggested that there is a bi-directional causation between the Islamic stock market and economic growth and between the Á sukūk market and economic growth in Indonesia.…”
Section: Islamic Finance and Economic Growthmentioning
confidence: 99%